2021
DOI: 10.1111/1442-1984.12323
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the reproductive biological characteristics of the alien invasive Coreopsis lanceolata to those of the non‐invasive alien congener Coreopsis tinctoria

Abstract: It is important to determine the characteristics associated with the success of alien species. However, there is no universal syndrome of invasion reproductive characteristics to explain the success of invasiveness has not been identified. Comparative studies on congeneric successful or non‐successful alien species are beneficial for revealing the drivers of invasion success and predicting future distributions. Reproductive biological characteristics, including the mating system, phenology of flowering, floral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(62 reference statements)
1
5
2
Order By: Relevance
“…Moreover, the results of the present study are in contrast to an earlier study in the introduced range of China, where no species of halictid bees had been observed (Zeng et al 2021). In China, Apis cerana (Apidae family) is the most important visitor of C. lanceolata (Zeng et al 2021).…”
Section: Floral Visitationcontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, the results of the present study are in contrast to an earlier study in the introduced range of China, where no species of halictid bees had been observed (Zeng et al 2021). In China, Apis cerana (Apidae family) is the most important visitor of C. lanceolata (Zeng et al 2021).…”
Section: Floral Visitationcontrasting
confidence: 99%
“…Coreopsis lanceolata (Asteraceae) is an herbaceous perennial up to 70 cm in height, which produces a mass of flower heads at densities of approximately 30 capitula per 100 cm 2 (Zeng et al 2021). Each capitulum comprises numerous ray and disk florets arranged into an entire inflorescence resembling a single flower (Fig.…”
Section: Study Species and Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely distributed mainly in the Americas and East Asia. In Korea, yellow flowers bloom in May-July [7]. The phytochemical constituents of CL flowers (CLF) have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%